Comparative Analysis of Transportation Methods in Order to Minimize Distribution Costs - Haryadi, Dudi; Hasanah, Uswatun (Bandung: Prodi Manajemen FE Universitas Langlangbuana, 2024)
For the company to progress and develop, in addition to improving its production process, the company must always pay attention to the distribution of the products produced. The company must choose and determine which method to use. The transportation method used will affect the price of the product sold to consumers. This study aims to determine the transportation or distribution model of the OSAD rice milling factory in Bandung Regency. The company makes total shipments from three rice milling factory warehouses to several marketing destinations, namely: Bandung, Bandung Regency, Cimahi, and Bandung Regency. West Bandung, then used three types of transportation methods, namely the North West Corner Method (NWCR, the Least Cost Method, and the third is Vogel's Approximation Method (VAM). The results of the three methods are then compared with the shipping costs usually carried out by the company, namely shipping with costs that always change depending on the bargaining with the shipping service. The results of this study are, using NWCR: Rp. 2,900,000, using Least Cost: Rp. 2,530,000, while using VAM: Rp. 2,520,000. so the cheapest shipping cost from the three factories is using Vogel's Approximation Method (VAM). The results of the three methods are cheaper when compared to the shipping that the company usually does before using the three methods, which ranges from Rp. 3,000,000 to Rp. 4,000,000